Strategi dan Tantangan Operasional pada KSU BONA MANDIRI JAYA di Kota Pematangsiantar - Dina Saragih; Roni A Hasibuan; Dian G Purba; Grace R Naibaho; Savirgi B Amri; Stepan H Purba; Ahmad Tarez Azhadi; Sintong B Simanjuntak; Tia saragih (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to analyze the marketing strategies, operational mechanisms, and key challenges faced by the Multipurpose Cooperative (KSU) BONA MANDIRI JAYA. A qualitative research approach was employed, utilizing in-depth interviews, direct observation, and document analysis as data collection methods. The results show that the cooperative adopts a direct marketing strategy targeting underserved and remote areas, combined with a personalized approach in monitoring its clients. Despite its growth, the cooperative encounters several challenges, including limited capital, low member financial literacy, non-performing loans, and the need to adapt to digital transformation. To overcome these obstacles, the cooperative implements credit restructuring policies and intensive field monitoring. The study recommends strengthening institutional capacity and adopting digital systems to enhance the sustainability and efficiency of cooperative operations.